FAULT DIAGNOSIS NEW METHOD OF ROLLING BEARING BASED ON ADAPTIVE REDUNDANT LIFTING SCHEME PACKET - XIAO ShunGen; SONG MengMeng; LAI LianFeng (Jixie qiangdu, 2015)
Aiming at feature identification of weak signal for rolling bearing fault,an adaptive redundant lifting scheme packet（ ARLSP） diagnostic method of undecimated operation was proposed to solve the faults distortion that caused by traditional wavelet packet or lifting wavelet transform using sample operation.ARLSP was based on the principle of lifting scheme.Initial undecimated prediction and update operator were calculated by Lagrange interpolating subdivision,and then constructed an ARLSP decomposition and reconstruction algorithm.Simulation signals were tried out by denoising and anti frequency aliasing,results show that ARLSP method was superior to the traditional wavelet packet in denoising capabilities,and there are no frequency aliasing.Moreover,taking an experiment on an asynchronous motor,the vibration signals of the rolling bearings 6205 under conditions of no fault,the inner ring fault,outer ring fault and rolling fault were measured.ARLSP method has been successfully used to extract characteristic frequency and frequency multiplication for various faults,and has got a higher diagnostic accuracy than traditional wavelet packet.